Electrochemical Energy Storage Studies on Sustainably Synthesized Co3O4 Nanoparticles for Supercapacitor Electrodes - Osora, Helen; Immanuel Edison, T. Jebakumar; Kolkoma, David; Anduwan, Gabriel; Waimbo, Mathew; Velusamy, Senthilkumar (New Environmentally-Friendly Materials, 2025)
In this study, a facile hydrothermal technique was used, and the commercially important cobalt oxide nanoparticles were synthesised for pseudocapacitor electrodes in supercapacitor applications. The prepared particles were subjected to different characterization techniques to determine their phase structure, topography, and elemental composition by XRD, FE-SEM, TEM, and EDAX. The XRD pattern confirmed the formation of pure cubic spinel Co₃O₄ phase with well-defined diffraction peaks and without any impurity phases, indicating high crystallinity of the synthesized nanoparticles. In addition, Raman spectroscopy exhibited prominent vibrational modes at around 469, 514, and 684 cm⁻¹, corresponding to the F₂g and A₁g modes of the spinel Co₃O₄ structure, further confirming the successful formation of phase-pure cobalt oxide with strong crystalline quality. Further, the particles electrochemical properties were investigated in an alkaline electrolyte at 3 M. The electrochemical studies confirmed that during galvanostatic charge and discharge studies, the built electrode displays a maximal specific capacitance value of 450 Fg⁻¹ at 6 Ag⁻¹. In addition, the cyclic stability experiments confirmed that the prepared electrode exhibits a retaining ability of 87% even after cycles at 10 Ag⁻¹. Further, the constructed symmetrical structure achieved a highest power density of 1312 W kg⁻¹ with an energy density of 19 Wh kg⁻¹, measured at a current density of 10 Ag⁻¹. These results demonstrate that hydrothermally synthesized Co₃O₄ nanoparticles are promising, low-cost, environmentally benign electrode materials for high-power supercapacitor applications such as power buffering in renewable-energy systems and short-duration backup for portable electronics.